Nanoscale Effects in One‐Dimensional Columnar Supramolecular Ferroelectrics. Issue 48 (8th August 2019) - Anetai, Hayato; Sambe, Kohei; Takeda, Takashi; Hoshino, Norihisa; Akutagawa, Tomoyuki
Abstract: Organic ferroelectrics have been actively developed with the goal of fabricating environmentally friendly and low‐cost memory devices. The remanent polarization of hydrogen‐bonded organic ferroelectrics approaches that of the inorganic ones. Nanoscale fabrication of organic ferroelectrics is an essential aspect of high‐density memory devices. A pyrene derivative with four tetradecylamide (−CONHC14 H29 ) chains (1 ) formed an amide‐type N−H⋅⋅⋅O hydrogen‐bonded one‐dimensional (1D) column, which demonstrated ferroelectricity in the discotic hexagonal columnar (Colh ) liquid crystalline phase through the inversion of the orientation of the hydrogen‐bonded chains. On the contrary, similar chiral pyrene derivatives bearing 3, 7‐dimethyl‐1‐octhylamide chains ( S ‐2 and R ‐2 ) did not indicate the Colh phase and ferroelectricity. Homogeneous mixed liquid crystals (1 )1− x (S‐2 ) x (i.e., between the ferroelectric1 and the non‐ferroelectric S ‐2 ) enable the control of the nanoscale aggregation state of the organic ferroelectrics, resulting in a nanoscale effect of the 1D supramolecular ferroelectrics. Ferroelectric mixed liquid crystals (1 )1− x (S‐2 ) x were observed at x ≦0.03, where one S ‐2 molecule was inserted after every thirty‐three1 molecule in the mixed liquid crystal (1 )33 ( S ‐2 ). An average (1 )34 length of approximately 12 nm was required to maintain the 1D ferroelectricity, which was similar to the nanoscale limit of inorganic ferroelectrics, such as hafnium oxide thin film (≈15 nm). Abstract : Under control : Homogeneous mixed liquid crystals (1 )1− x ( S ‐2 ) x (ferroelectric1 and non‐ferroelectric S ‐2 ) enable the control of the nanoscale aggregation state of organic ferroelectrics, resulting in a nanoscale effect of the one‐dimensional (1D) supramolecular ferroelectrics (see figure).